2016
DOI: 10.1021/acsenergylett.6b00549
|View full text |Cite
|
Sign up to set email alerts
|

Study of Electrochemical Phenomena Observed at the Mg Metal/Electrolyte Interface

Abstract: The interface between Mg metal and electrolyte is a key factor affecting Mg battery performance. Switchable interfacial phenomena, involving apparent surface electrochemical inhibition under open-circuit voltage and reactivation upon electrochemical polarization, were investigated with various Mg electrolyte systems, under both electrochemically static and dynamic conditions. Most notably, it was found that such behavior appears to be unique for the Mg system, implying that correct control of the interface is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
150
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(163 citation statements)
references
References 60 publications
11
150
0
2
Order By: Relevance
“…Mg electrodes aged in electrolytes with different iodine concentrations were examined using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) ( Figure S2, Supporting Information). [22,26] According to a previous systematic XPS study of Mg metal, this surface layer could only be a few nanometer thick. To obtain a finer picture of the surface chemistry of the Mg electrodes in the electrolytes with low iodine concentrations, we performed X-ray photoelectron spectroscopy (XPS).…”
mentioning
confidence: 99%
“…Mg electrodes aged in electrolytes with different iodine concentrations were examined using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) ( Figure S2, Supporting Information). [22,26] According to a previous systematic XPS study of Mg metal, this surface layer could only be a few nanometer thick. To obtain a finer picture of the surface chemistry of the Mg electrodes in the electrolytes with low iodine concentrations, we performed X-ray photoelectron spectroscopy (XPS).…”
mentioning
confidence: 99%
“…The hexacoordinate cluster of Mg 2+ (G1) 3 -6C has been observed as part of the crystal structure of Mg(BH 4 ) 2 in G1. 51 Interestingly, whenever the magnesium atom is coordinated by an odd number of oxygens, implying a dangling uncoordinated oxygen as G1 has two oxygens, the free energy associate this oxygen is always exothermic. This demonstrates that clusters in which all solvent oxygens are chelated to magnesium are more stable.…”
Section: Resultsmentioning
confidence: 99%
“…The patchy deposition of Mg provides additional evidence that electrolyte and Cu electrode are not in contact over the full area, but that the contact area increases upon plating, as the plated Mg fills the gaps between electrolyte and electrode. Also for liquid electrolyte systems it has been observed that newly formed interfaces between Mg metal and electrolyte improve the performance24.…”
mentioning
confidence: 99%